Towards the automatic analysis of NMR spectra part 7. Assignment of 1H by employing both 1H and 1H/13C correlation spectra - Griffiths, Lee (Magnetic resonance in chemistry : MRC, 2008)
2008 John Wiley & Sons, Ltd.